Effect of Antenatal Dexamethasone on Serum Umbilical Cord C-peptide and Glucose Levels in Term Neonates Delivered by elective Cesarean Section - Ramadan Mahmoud; Magdy A Mohamed; Shereen P Aziz (Mashhad University of Medical Sciences, 2018)
Background: Antenatal steroid therapy recently has been considered for term and late preterm neonates delivered by Cesarean section (CS), with the aim of preventing adverse respiratory morbidity. The main aim of this study was to investigate the metabolic effects of antenatal dexamethasone on blood glucose (BG), homeostasis, and serum C-peptide level when administered to term fetuses. Methods: Umbilical cord blood C-peptide and BG were measured in singleton newborns of 37 weeks gestational age or older with planned CS; furthermore, the history of dexamethasone receiving was taken from mothers. Other parameters, such as, Apgar score, neonatal birth weight, BG follow-ups, and admission to the neonatal nursery were collected. Results: Totally, 117 mothers met the inclusion criteria, of whom 60 had received antenatal dexamethasone. This study demonstrated that babies treated with antenatal dexamethasone had a decrease in umbilical cord BG (P=0.001) and BG follow-up three hours after birth (P=0.001) compared to untreated group. However, there was no statistically significant difference in the BG measurements within both groups in the first 24 h post birth (P=0.14). Furthermore, no statistically significant difference was observed within the two groups regarding umbilical cord C-peptide measurements (P=0.08), birth weight (P=0.17), and the numbers of neonates that needed admission to the nursery (P=0.36). Conclusion: Although antenatal dexamethasone causes immediate mild BG homeostasis alterations in term newborns delivered by elective CS, its use is not associated with a statistically significant effect on serum umbilical cord C-peptide measurements, neonatal birth weight, and the rate of neonatal nursery admission.